Ballistic performance and energy absorption characteristics of thin nickel-based alloy plates at elevated temperatures. (April 2019) - Liu, Jiao; Zheng, Bailin; Zhang, Kai; Yang, Biao; Yu, Xiaoqiang
Abstract: To study the aeroengine containment capability at high temperatures, experimental and numerical investigations have been carried out to determine the ballistic performance and energy absorption characteristics of GH4169 alloy thin plates at temperatures ranging from 25–600 °C. First, experiments were conducted using a gas gun. Target plates were impacted by projectiles with various initial velocities. The effects of the temperature and initial velocity on the deformation, failure pattern and energy absorption of the plate were correspondingly obtained. The experimental results showed that at higher temperature, the deformation of the target plates is greater, the energy absorbed by the target plates is smaller and the ballistic limit velocities are lower. The petal deformation of the target plate caused by bending is severe at the temperature of 600  °C. Second, numerical simulations of the impact were conducted by an explicit dynamics FE code (LS-DYNA). The Johnson-Cook constitutive model with parameters obtained from split Hopkinson pressure bar (SHPB) experiments was used to describe the materials properties of the plates at various temperatures and strain rates. It was found that the numerical results are consistent with those obtained by the ballistic experiments. In addition, the results of the numerical simulations also showed that the ballistic limit velocity of the target plate exhibits an approximately linear relationship with the temperature of the target plate. The energy absorbed by the target plate is decreased by 18% and 9% at 600 °C and 300 °C, respectively, compared with that at 25 °C.